2013
DOI: 10.1002/adfm.201202689
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Doping in Planar Ionic Transition Metal Complex‐Based Light‐Emitting Electrochemical Cells

Abstract: Using a planar electrode geometry, the operational mechanism of iridium(III) ionic transition metal complex (iTMC)‐based light‐emitting electrochemical cells (LECs) is studied by a combination of fluorescence microscopy and scanning Kelvin probe microscopy (SKPM). Applying a bias to the LECs leads to the quenching of the photoluminescence (PL) in between the electrodes and to a sharp drop of the electrostatic potential in the middle of the device, far away from the contacts. The results shed light on the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 53 publications
(98 reference statements)
3
67
0
Order By: Relevance
“…This may be rationalized by the fact that p-doping initially dominates in the iridium(III)-based iTMC-LEC and hence the onset of light emission occurs in close proximity to the metal electrode. 21 As metals are known to heavily quench the luminescence of organic compounds, the emission zone has to move away first before light emission can be detected, which is why the turn-on time is longer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be rationalized by the fact that p-doping initially dominates in the iridium(III)-based iTMC-LEC and hence the onset of light emission occurs in close proximity to the metal electrode. 21 As metals are known to heavily quench the luminescence of organic compounds, the emission zone has to move away first before light emission can be detected, which is why the turn-on time is longer.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] Subsequent electrochemical doping of the luminescent, semiconducting material used, manifested via its reduction and oxidation by injected electrons and holes and the simultaneous compensation of the generated charge by ions with opposite sign, gives rise to the in situ formation of highly conductive p-and n-type regions adjacent to the anode and cathode, respectively, which grow towards each other to finally establish a light-emitting p-i-n junction, where charge carriers recombine radiatively. 9,10,20,21 The peculiar functional principle of LECs is responsible for their beneficial properties, like low-voltage operation and bipolar electroluminescence almost irrespective of the work-function of the electrode materials used, 9,10,22,23 but has been the subject of intense debates ever since their discovery by Pei et al in 1995. [24][25][26] Recent studies, however, have unequivocally confirmed the working mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Device preparation: The conjugated polymer used in the active layer of the sandwich LECs is Computational details: For the numerical simulations, a 2-dimensional drift-diffusion model was used [21] which is described in detail in section A of the Supporting Information. Here Exciton quenching by polarons is described by diffusion-mediated Förster resonance energy transfer.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, both light intensity and EQE are significantly enhanced for the hybrid device as compared to the LEC reference, especially directly after device turn-on (see Figure 5, panels b and c). Since electrons are believed to be the minority charge carriers in iTMC-LECs, 29,60 and particularly in the case of the selected iTMC-emitter, 61 an increase of light intensity by several orders of magnitude in the range of 0−5 min should be attributed to an improved electron injection. The positions of HOMO and LUMO levels of the iTMC, as shown in Figure 1c, support the assumption of improved electron injection by the QD layer into the iTMC layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%